A2.42 Clinical utility of measuring naÏve CD4+T-cell in early ra patient to predict remission on mtx: A replication study. (24th February 2016) - Ponchel, F; Hunt, L; Burska, AN; Parmar, R; Buch, MH; Emery, P
Abstract : Objectives: The current optimal therapeutic approach in early rheumatoid arthritis (RA) is to start Methotrexate (MTX) to target inflammation and induce remission. Prediction of MTX therapy response remains a key clinical need to enable the identification of patients who would benefit from an alternative, more aggressive treatment strategy. T-cell subset analysis has been shown to have biomarker value in predicting MTX remission in early RA. 1 Given the clinical importance of these findings, our aim was to validate the original data 1 using T-cell subset quantification this time performed solemnly by routine hospital services, in order to replicate these original findings and validate naïve T-cell frequencies as biomarker of the the achievement of clinical remission with MTX treatment in early RA. Methods: T-cell subsets were quantified in 70 drug-naïve early RA patients, commencing MTX. The primary outcome was remission (DAS28 < 2.6) after 6 months. We used previously established reference range (using 120 healthy controls) for inflammation related cells (IRC) and corrected for age variation in naïve and regulatory (Treg) T-cells. Logistic regressions were used to model the remission outcome. Results: Remission was achieved in 37/70 patients. In univariate analysis, the achievement of remission was strongly associated with age-corrected naïve CD4 + T-cell frequency and current not-smoking (p < 0.0001), as well as weakly with high frequency of IRC, CRP or DAS28 (p ≤ 0.101). A model using age-corrected naive frequency, currently not-smoking and DAS28 correctly predicted remission in 88.4% of patients. Dichotomising naïve T-cell frequency using the age-related reference line (at 1% above 95% CI), confirmed a sensitivity/specificity 78%/81%, PPV/NPV 78%/81% and OR 15.4 (95% CI 5.02–53.55), p < 0.0001. Conclusion: This study confirms the ability of baseline naïve T-cell subset analysis in predicting early RA remission with first-line MTX therapy, suggesting clinical utility for the selection of the most appropriate therapy at disease presentation. All data being acquired by hospital routine services, they should be transferable widely towards personalised medicine. Reference: Ponchel F, Goëb V, Parmar R, et al . An immunological biomarker to predict MTX response in early RA. Ann Rheum Dis 2014;73(11):2047–53